Increase in optic nerve sheath diameter predicts early cerebral involvement in fat embolism syndrome - Arnab Banerjee; Richa Aggarwal; Kapil dev Soni; Anjan Tirkha (Chinese Journal of Traumatology, 2021)
Early diagnosis of cerebral fat embolism in a patient with contradiction to MRI is challenging. Here we report an interesting case, where the raised optic nerve sheath diameter helped us to predict the early cerebral involvement with fat emboli in a left femoral shaft fracture patient. MRI scan could not be performed due to the presence of a metallic implant in the patient from a previous surgery. He was later diagnosed as an atypical presentation of fat embolism syndrome. Optic nerve sheath monitoring also helped us to guide further management of the patient.